Fish fauna diversity of Karamana River, Kerala, India: A study - Jancy Rani A.K; Jobiraj (Advances in Aquaculture and Fisheries Management, 2017)
This study on Fish diversity of Karamana river was carried out from October 2015 and September 2016. The fish diversity is correlated with biological and various physio-chemical parameters that regulate the productivity and distribution of different species of fishes. The fish population is abundant and majority of the fishes are exploited for human consumption. For the purpose of the study, attempts were made to collect, classify and identify fish of river Karamana in three zones. The major fish abundance was noticed in the family Cyprinidae; several species of fish belonging to the different order were present. They were Anguliformes, Belonifoemes, Cypriniformes, Cryprinodontiformes, Peraciformes, Siluriformes, Synbranchiformes. The fish species diversity was found decreasing in March and was the highest in October in the year 2015-2016. Among the families of fishes collected Cyprinidae was the most dominant (41.55%), followed by Cichlidae (25.98%), Mugilidae (14.66%) Bagridae (3.33%), Channidae (3.13%), Siluridae (2.31%), Nandidae (1.79%), Godiidae (1.71%), Clariidae (1.41%), Ambassidae (0.91%), Aploecheilidae (0.80), Heteropneustidae (0.61%), Mastacembelidae (0.61%), Balitoridae (0.60%). The least were observed in Anguillidae (0.30%), Belonidae (0.20%) and Cobitidae (0.10%). The data shows the rivers are dominated by Cyprinidae with more ornamental fishes than cultivable and food fish. The Cichliddae family that dominates second has three species that are cultivable and food fish. The main reasons behind the decline of species are habitat destruction, introduction of exotic species, pollution and over fishing. Proper conservation methods and prevention of pollution can increase the number of food fish and cultivable fishes in the river. Information about the demography of the important threatened fishes points to the lack of conservation efforts. The result of the present study provides an insight on fish diversity of Karamana river, its proper management and the importance to conserve the fish diversity.